Efforts to Cultivate Empathy and Collaboration Through Project-Based Social Learning in Inclusive Elementary Schools - Anisah Jayanti; Muhammad Fauzan Muttaqin (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze the effectiveness of Project-Based Social Learning in fostering empathy and collaboration among students in inclusive elementary schools. The research employed a library research method by reviewing a range of literature sources including scientific journals, books, and previous studies relevant to inclusive education and project-based learning strategies. The findings indicate that Project-Based Social Learning is able to encourage positive interaction among students, stimulate social awareness, and train collaborative skills in completing group tasks. Furthermore, its implementation in inclusive elementary school settings is considered effective, as it provides opportunities for students with special needs to actively participate according to their abilities and potentials, which consequently leads to an increase in empathy and the development of a collaborative culture in the school environment. Therefore, Project-Based Social Learning is deemed an appropriate instructional approach for elementary school teachers to build empathy and collaboration in a sustainable manner.